1983
DOI: 10.1159/000225692
|View full text |Cite
|
Sign up to set email alerts
|

Antigrowth Effect of Some Inhibitors of Polyamine Synthesis on Transplantable Prostate Cancer

Abstract: Inhibitors of polyamine synthesis were tested for therapeutic effectiveness on transplantable prostate cancer. Inhibition of either ornithine decarboxylase or S-adenosyl-L-methionine decarboxylase (AMDC) by α-difluormethylornithine (DFMO) or methylglyoxal-bis[guanylhydrazone] (MGBG), respectively, was associated with significant antitumor effect. The combination of DFMO with MGBG was not only more effective but no more toxic than MGBG alone. Combination of MGBG with 9-B-D-arabinofuranosyladenine, an indirect e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
2

Year Published

1984
1984
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 10 publications
0
9
0
2
Order By: Relevance
“…This occurred even in patients in whom the DFMO was clearly acting effec tively as an ODC inhibitor, as evidenced by the decline achieved in the cellular po lyamine levels during the pretreatment period. Administration of MGBG to animals promotes large increases in the putrescine levels of rat intestinal mucosa [30], mouse brain [14], ventral prostate [18], spleens of LI210 leukemia-bearing mice [11], and transplantable prostate cancer [7], How ever, in contrast to the present findings in humans, all of the animal studies, except that done with ventral prostate, found that MGBG promoted a decrease or no change in tissue spermidine levels and little change in spermine levels. Administration of MGBG to animals promotes an in crease in tissue activities of both ODC [7,9,12,14,18,30] and AMeDC [9,15,18,27,30] providing a potential explanation for the increased cellular polyamines noted in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…This occurred even in patients in whom the DFMO was clearly acting effec tively as an ODC inhibitor, as evidenced by the decline achieved in the cellular po lyamine levels during the pretreatment period. Administration of MGBG to animals promotes large increases in the putrescine levels of rat intestinal mucosa [30], mouse brain [14], ventral prostate [18], spleens of LI210 leukemia-bearing mice [11], and transplantable prostate cancer [7], How ever, in contrast to the present findings in humans, all of the animal studies, except that done with ventral prostate, found that MGBG promoted a decrease or no change in tissue spermidine levels and little change in spermine levels. Administration of MGBG to animals promotes an in crease in tissue activities of both ODC [7,9,12,14,18,30] and AMeDC [9,15,18,27,30] providing a potential explanation for the increased cellular polyamines noted in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Even though testosterone-induced growth of rat ventral prostate and seminal vesicle appears to respond poorly to the antiproliferative action of polyamine anti-metabolities (with the possible exception of difluoromethylornithine-induced diminution of prostatic secretion), a few reports indicate that experimental tumours of prostatic origin may be especially sensitive to the combined action of difluoromethylornithine and methylglyoxal bis(guanylhydrazone) when transplanted subcutaneously (Dunzendorfer et al, 1983;Herr & Kleinert, 1983). Of special interest is the report by Herr & Kleinert (1983) showing that the toxicity of methylglyoxal bis(guanylhydrazone) can be dramatically decreased, without lowering the dose, by combining the drug with difluoromethylornithine.…”
Section: Discussionmentioning
confidence: 99%
“…Growth of prostatic cancer cells transplanted subcutaneously in rats was inhibited by combined treatment with these two polyamine anti-metabolites (Dunzendorfer et al, 1983;Herr & Kleinert, 1983 for 20min in the cold. The enzyme activities and the content of difluoromethylornithine were assayed in the supernatant fraction.…”
mentioning
confidence: 99%
“…In den Tumoren wurden die Polyamine Putrescin und Spermidin be stimmt. Daneben wurden die enzymatischen Aktivitä ten der ODC und der SAMDC in modifizierter Form, wie mitgeteilt, ermittelt [16,17] …”
Section: Materials Und Methodikunclassified
“…Spermin [1,2,9], Die Aktivität der ODC ist in Tumoren gesteigert, und erhöhte Konzentrationen von Putrescin und Spermidin sind bei allen bisher untersuchten Tumorgeweben nachgewiesen worden. Dabei ist regelmässig festzustellen, dass die Wachstumsrate von Tumoren von der intrazellulären Polyaminkonzentration abhängt [10][11][12][13], Die Konzentrationen von Putrescin, Sper midin und Spermin im Gewebe der Ratten prostata sind signifikant höher als in allen anderen Organen, und es ist bekannt, dass Polyamine in hoher Konzentration im Sperma Vorkommen und dort nutritive wie stabilisierende Funktionen ausüben [14], Die Konzentrationen der Polyamine im mensch lichen Prostatagewebe sowie die 24-StundenAusscheidung von Polyaminen bei Patienten mit Prostatakarzinomen stimmen mit den bisherigen Ergebnissen über Polyamine und Tumorstoffwechsel überein [14,15] [16,17], Die begrenzten therapeutischen Möglich keiten des metastasierenden hormonrefraktä ren Prostatakarzinoms bei Männern unter 60 Jahren lassen eine präklinische Untersu chung mit Inhibitoren der Omithindecarboxylase durch Alpha-Difluoromethylomithin (DFMO) und S-Adenosylmethionindecarboxylase durch Methylglyoxal-bis-guanylhydrazon (MGBG) als wichtig erscheinen.…”
unclassified